Removal of Cadmium from Water by CNT-PAC Composite: Effect of Functionalization - AlSaadi, M.A.; Al Mamun, A.; Alam, M.Z.; Amosa, M.K.; Atieh, M.A. (World Scientific Publishing, 2016)
Cadmium (Cd2+) is one of the toxic heavy metals that is frequently used in many industrial products. The wastewater from these industries and their products contains residual cadmium that are difficult to be removed economically from the effluent. Carbon nanotubes (CNTs) were synthesized in several batches and tested for their removal efficacy with regards to cadmium removal from synthetic wastewater. Fixed catalyst chemical vapor deposition (FCCVD) reactor system was fabricated in the laboratory for the synthesis of CNTs on the powdered activated carbons (PACs). The PACs were impregnated with Fe3+ catalysts, and growth parameters such as the reaction time, gas flow rates and reaction temperature were optimized. The sorption capacity of the raw CNT-PAC was not satisfactory until the sorbents were functionalized which eventually led to high adsorption capacities. The surface properties of CNT-PAC were modified by oxidative functionalization using two different methods: sonication with KMnO4 and refluxing with HNO3 at 140°C. KMnO4-treated CNT-PAC exhibited the highest sorption capacity for cadmium uptake which increased from 4.77mg/g (untreated CNT-PAC) to 11.16mg/g; resulting in Cd2+ removal efficiency from 38.87% to 98.35%.